Perception of freedom in the Chinese linguistic worldview: Tradition and modernity - K.M. Naumova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article examines the changes in the linguistic and cultural concepts of freedom (自由 zìyóu) in the Chinese linguistic worldview, which have occurred as a result of extralinguistic and socio-cultural transformations brought by globalization processes between the 20th and 21st centuries. The starting point of the research is the traditional ideas about freedom, rooted in Confucianism and the Taoist worldview, according to which disobedience and self-will of the individual can lead society and the country to chaos, so freedom should be limited by norms and prohibitions. By studying empirical data with the help of definitional, quantitative, interpretative, and contextual analysis, a total of more than 1000 phrases with the lexical unit of interest were gathered. Thus, the idea of freedom in modern Chinese society was described in great detail. The results obtained were accompanied with the data of the quantitative analysis of the most frequent collocations based on the materials of the Balanced Corpus of Modern Chinese in Peking University. The article provides many examples that prove that the lexeme 自由 zìyóu occurs in phrases that describe numerous and diverse spheres of human activity. The conclusion was made that it has expanded its combinability capabilities as a result of the semantic shift that took place with the penetration of liberal ideas into China from the West. The research is of great importance and benefit for Chinese philologists, as well as for anyone interested in studying globalization processes and their impact on the traditional cultures of the East.